2018
DOI: 10.1093/brain/awy260
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 mutations increase HNRNP A1-7B through gain of splicing function

Abstract: In a recent investigation Deshaies and colleagues identify HNRNP A1-7B, an isoform of the RNA binding protein (RBP) HNRNP A1, as present in post mortem amyotrophic lateral sclerosis (ALS) spinal motor neuron inclusions (Deshaies et al., 2018). HNRNP A1 is an important player in ALS, as mutations in its low complexity domain (LCD) can be causative for the disease (Kim et al., 2013). Intriguingly, the isoform described by Deshaies et al.includes exon 7B, which produces an extension of the LCD by 52 amino acids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In addition, ZV & FA extracts showed more protection against seizures and mortality in picrotoxin-induced seizure model as compared to strychnine-induced seizure model at high doses (Figure 3). [44,45]. Future studies could be designed to determine the GABAergic potential of these extracts for better mechanistic insights.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ZV & FA extracts showed more protection against seizures and mortality in picrotoxin-induced seizure model as compared to strychnine-induced seizure model at high doses (Figure 3). [44,45]. Future studies could be designed to determine the GABAergic potential of these extracts for better mechanistic insights.…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate the interest taken by Dr Fratta and his team (Sivakumar et al, 2018) in our recent work documenting the impact of TDP-43 on the splicing of hnRNP A1 and its potential relevance in the pathogenesis of amyotrophic lateral sclerosis (ALS) as outlined in our paper 'TDP-43 regulates the alternative splicing of hnRNP A1 to yield an aggregation-prone variant in amyotrophic lateral sclerosis' (Deshaies et al, 2018). Indeed, their letter highlights the complexity of RNA binding protein (RBP) functional networks.…”
Section: Sirmentioning
confidence: 93%
“…Under the current model for prionlike aggregation, the high-scoring protein isoform (which is typically less-abundant than the low-scoring isoform [88,89]) could "seed" protein aggregates, which may then be capable of recruiting the lower-scoring isoform. Although this is currently speculative, it is supported by a recent study, which showed that mutation in the TDP-43 PrLD and cytoplasmic aggregation of TDP-43 in ALS patients was associated with dysregulation of hnRNPA1 mRNA splicing [89,90]. This dysregulation led to increased abundance of the high-scoring hnRNPA1-B isoform and subsequent aggregation of the hnRNPA1 protein [89].…”
Section: A Survey Of Post-translational Modifications Within Human Prldsmentioning
confidence: 96%